Dual antiplatelet therapy duration after percutaneous coronary intervention in high bleeding risk: a meta-analysis of randomized trials. (7th December 2022) - Costa, Francesco; Montalto, Claudio; Branca, Mattia; Hong, Sung-Jin; Watanabe, Hirotoshi; Franzone, Anna; Vranckx, Pascal; Hahn, Joo-Yong; Gwon, Hyeon-Cheol; Feres, Fausto; Jang, Yangsoo; De Luca, Giuseppe; et al.
Abstract: Aims: The optimal duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in patients at high bleeding risk (HBR) is still debated. The current study, using the totality of existing evidence, evaluated the impact of an abbreviated DAPT regimen in HBR patients. Methods and results: A systematic review and meta-analysis was performed to search randomized clinical trials comparing abbreviated [i.e. very-short (1 month) or short (3 months)] with standard (≥6 months) DAPT in HBR patients without indication for oral anticoagulation. A total of 11 trials, including 9006 HBR patients, were included. Abbreviated DAPT reduced major or clinically relevant non-major bleeding [risk ratio (RR): 0.76, 95% confidence interval (CI): 0.61–0.94; I 2 = 28%], major bleeding (RR: 0.80, 95% CI: 0.64–0.99, I 2 = 0%), and cardiovascular mortality (RR: 0.79, 95% CI: 0.65–0.95, I 2 = 0%) compared with standard DAPT. No difference in all-cause mortality, major adverse cardiovascular events, myocardial infarction, or stent thrombosis was observed. Results were consistent, irrespective of HBR definition and clinical presentation. Conclusion: In HBR patients undergoing PCI, a 1- or 3-month abbreviated DAPT regimen was associated with lower bleeding and cardiovascular mortality, without increasing ischaemic events, compared with a ≥6-month DAPT regimen. Study registration: PROSPERO registration number CRD42021284004 Structured Graphical Abstract: Structured Graphical Abstract Impact of abbreviated vs. standard DAPT in patients at high bleeding risk undergoing coronary stenting.